First demonstration of radiative power exhaust with impurity seeding in the island divertor at Wendelstein 7-X. (22nd August 2019) - Effenberg, F.; Brezinsek, S.; Feng, Y.; König, R.; Krychowiak, M.; Jakubowski, M.; Niemann, H.; Perseo, V.; Schmitz, O.; Zhang, D.; Barbui, T.; Biedermann, C.; et al.
Abstract: Radiative power exhaust by impurity seeding was demonstrated for the first time in island divertor configurations at the stellarator Wendelstein 7-X. Feasibility of stable plasma operation was shown during seeding with both neon (Ne) and nitrogen (N2 ). High radiative power losses ( 80%) were found to reduce the divertor heat loads globally by 2/3 with both seeding gases injected at a single toroidal location into one of five magnetic islands. Heat flux detachment was achieved for the price of a loss of ( %) in the stored energy. Ne seeding allows for sustained enhancement of edge radiation with a very slow decay of line emission of several tens of seconds after the end of the injection indicating a high recycling of this noble gas at the carbon main plasma facing components. In N2 seeded discharges it is shown that a response of line emission and plasma parameters is in correlation to the puff duration which indicates a higher level of absorption of this seeding gas in the wall. Continuous N2 seeding results in global cooling of the scrape-off layer (SOL) and decay of radiation over several seconds after the injection. Damping of counter-streaming SOL flows, and divertor particle fluxes induced by Ne and N2 seeding have been measured and provide evidence for a reduction of the convective part of the divertor heat fluxes. Losses in density in response to seeding can be compensated by feedback controlled divertor fueling. The controlled reduction of heat fluxes within this complex 3D edge island geometry is a very promising finding concerning detachment control in a future all-metal divertor.